Electro synthesised NiTe2 Thin Films with the Influence of Additives - T., Joseph Sahaya Anand (2013)
Solar cell is one of the promising alternative green energy sources that can provide free electricity when sunlight is converted. The absorbent materials and their synthesis methods are subject of interest mainly due to solar panel installation cost despite of free electricity generated. The well-known silicon solar cells made, either amorphous or polycrystalline are good in conversion efficiency up to 17%, but their high cost make the researchers to look for new materials. Semiconducting materials in thin film form such as InP, SnO2¬ and ZnO are being studied as the alternative materials, but are not commercialised due to their poor conversion efficiency. Another group of semiconductor compounds known as transition metal chalcogenides (TMC) have been developed to be used as the absorbent materials. Consisting of transition metals and chalcogenides (S, Se and Te), they show promising solar absorbent properties such as semiconducting band gap, well adhesion to substrate and good conversion with better cost-effective. There are many TMC compounds synthesised, including copper indium selenide (CIS), ZnTe2, CdSe etc. Nickel, one of the transition metals synthesised with chalcogenides are referred as nickel chalcogenides. There are many possible combinations of nickel chalcogenides such as NiS2, NiSe, NiSe2 and Ni3Se2. The combination of nickel and telluride are the fewest being observed due to the nature of tellurium that is poorly-adhesive onto the substrate. Therefore, NiTe2 thin film is being synthesised onto the indium tin oxide (ITO) coated glass substrates and their properties are studied. There are many synthesis routes of thin film solar cells namely chemical bath deposition, electron sputtering, physical vapour deposition and chemical vapour deposition which requires the use of expensive machines, thus involving the high capital cost. Electrodeposition is introduced to cater the fabrication of thin films cost-effectively. Ability of large scale deposition, minimum waste of component and easy monitoring are among the advantages offered by this method. The present work is focusing on the NiTe2 synthesise through this route. The additives are being used to improve the adhesion between the film and substrate. Cyclic voltammetry experiments have been done prior to electrodeposition in order to get the electrodeposition potential range. The oxidation and reduction regions can obviously be seen in the range between -1.37 to -0.4 V and -0.4 to 0.98 V respectively. The electrodeposition is carried out using the potentials in the reduction region, producing the well-adherent, well-distributed and dark-coloured thin films.